The influence of morpho-anthropogenic indicators on the risk of damage to the musculoskeletal system and the working qualities of dogs - Goncharova D.A.; Slesarenko N.A. (Ветеринария и кормление)
It has been established that damage to the musculoskeletal system in sports and working dogs is due to the integration influence of a combination of both exo- and endogenous factors, including biomechanical (hypo- and hyperkinesia), psychoemotional, alimentary, genetic, which determine the intraspecific, pedigree, intrabreed, sexual, age and ethological characteristics of animals. Anatomical prerequisites for the risk of damage to the musculoskeletal system in sports and working dogs are the type of constitution (raw and tender), asymmetry, physique indices, as well as the growth and development of long tubular bones, reflecting the nature of their physiological restructuring. It was found that the type of constitution (raw and tender) indicates the direction of breeding and breeding work on the decorative appearance, rather than on the functional fitness of the musculoskeletal system and the working qualities of animals. Dogs with a strong and dry type of constitution (sanguine) were distinguished by greater speed, endurance and performance of performance indicators, stability and correctness of exercise, a high degree of adaptation, balance, adequacy of behavioral reactions and the ability to differentiate. A common phenomenon of congenital and acquired asymmetry (lateralization) has been identified, the type of which is confirmed by an established set of morphological (linear indicators of long tubular bones) and ethological (motor behavior, type of higher nervous activity, predominant behavioral reactions) indicators.